Rapid Stiffness Mapping in Soft Biologic Tissues With Micrometer Resolution Using Optical Multifrequency Time‐Harmonic Elastography - Jordan, Jakob; Jaitner, Noah; Meyer, Tom; Brame, Luca; Ghrayeb, Mnar; Köppke, Julia; Böhm, Oliver; Klemmer Chandía, Stefan; Zaburdaev, Vasily; Chai, Liraz; Tzschaetzsch, Heiko; Mura, Joaquin; et al. (Advanced Science, 2024)
Rapid mapping of the mechanical properties of soft biological tissues from light microscopy to macroscopic imaging can transform fundamental biophysical research by providing clinical biomarkers to complement in vivo elastography. This work introduces superfast optical multifrequency time-harmonic elastography (OMTHE) to remotely encode surface and subsurface shear wave fields for generating maps of tissue stiffness with unprecedented detail resolution. OMTHE rigorously exploits the space-time propagation characteristics of multifrequency time-harmonic waves to address current limitations of biomechanical imaging and elastography. Key solutions are presented for stimulation, wave decoding, and stiffness reconstruction of shear waves at multiple harmonic frequencies, all tuned to provide consistent stiffness values across resolutions from microns to millimeters. OMTHE's versatility is demonstrated by simulations, phantoms, Bacillus subtilis biofilms, zebrafish embryos and adult zebrafish, reflecting the diversity of biological systems from a mechanics perspective. By zooming in on stiffness details from coarse to finer scales, OMTHE has the potential to advance mechanobiology and offers a way to perform biomechanics-based tissue histology that consistently matches in vivo time-harmonic elastography in patient
Keywords: biofilms; multifrequency shear waves; optical microscopy; soft tissue stiffness; time harmonic elastography; elastography; zebrafish